Kearifan Lokal ”Kabus” dalam Perlindungan Sumberdaya Alam: Studi Suku Beser Betew di Kampung Tolobi Distrik Kofiau Kabupaten Raja Ampat - Maruapey, Azis; Kamaluddin, Kamaluddin; Lestaluhu, Rajab; Saeni, Fajrianto; Saeni, Agil (Universitas Muhammadiyah Sorong, 2025)
Kabus in Kofiau, Raja Ampat Regency is a traditional tradition that aims to preserve natural resources in the form of forests and seas. This Kabus has long been initiated by indigenous communities and religious leaders, and is supported by the local government and The Nature Conservancy (TNC). This research was conducted on the